2014
DOI: 10.1002/mrm.25245
|View full text |Cite
|
Sign up to set email alerts
|

Combined intravoxel incoherent motion and diffusion tensor imaging of renal diffusion and flow anisotropy

Abstract: Both flow and microstructure apparently contribute to the medullary diffusion anisotropy. The described novel method may be useful in separating decreased tubular flow from irreversible structural tubular damage, for example, in diabetic nephropathy or during allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
108
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(121 citation statements)
references
References 42 publications
11
108
2
Order By: Relevance
“…Another limitation of the study is that we used a minimum number of diffusion directions with only one b value to control the acquisition time which could have influenced flow effects. A basic approach to separate contributions of diffusion and perfusion to diffusion images is by using multiple b values with a biexponential fit [9,30,33]; this will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the study is that we used a minimum number of diffusion directions with only one b value to control the acquisition time which could have influenced flow effects. A basic approach to separate contributions of diffusion and perfusion to diffusion images is by using multiple b values with a biexponential fit [9,30,33]; this will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy kidneys have a well-defined structure with radial orientation of tubules, collecting ducts and blood vessels in the medulla, which makes diffusion properties in the medulla demonstrate obvious anisotropy. In healthy kidneys, FA of the medulla is higher than that of the cortex, and the repeatability, low interobserver and low intraobserver variability have been proved in many studies [2][3][4][5][6][7][8][9]. Recent studies have demonstrated the ability of renal DTI to detect renal damage in chronic kidney diseases, diabetic nephropathy, glomerulonephritis and renal masses [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 93%
“…Further, recent studies show that renal ADC values correlate with histological measures of fibrosis in patients with CKD and experimental renal disease [22, 2729]. Also, IVIM imaging was recently applied to characterize changes in renal perfusion, tubular flow, and tissue diffusion that are associated with renal structural damage [30, 31]. The data suggested that renal perfusion is reduced earlier and affected more than molecular diffusion during renal disease progression.…”
Section: Assessment Of Renal Injury and Fibrosismentioning
confidence: 99%
“…On the contrary, separation of perfusion from diffusion requires high signal-to-noise ratios, and there are some technical challenges to overcome, such as artifacts from other bulk flow phenomena including vascular tubular flow and glandular secretion, which are difficult to separate from microcapillary perfusion (16). Another technical challenge may be that IVIM has a different sensitivity to vessel sizes, according to the range of b values.…”
Section: Pathophysiologic Hot Spots and Consideration Of Emerging Tecmentioning
confidence: 99%
“…The authors of several, published studies (141516) have shown that APT imaging allows the detection and characterization of malignant brain tumors. In addition, APT asymmetry values have been proposed as prognostic indicators of brain glioma as they reflect the cellular proliferation levels that correlate with Ki-67 (17), and function as sensitive biomarkers of treatment response (18) in experimental and clinical studies.…”
Section: Current Clinical Hotspots Of Emerging Imaging Techniques In mentioning
confidence: 99%